Screening of Antibacterial Activity of Various Extractives of Seeds of Cassia tora and Alternanthera sessilis - Sahu, B.R.; Chakrabarty, Ajita (Asian Journal of Chemistry, 2010)
Various seeds extracts of Cassia tora and herb extracts of Alternanthera sessilis were tested against some human and plant pathogenic bacteria, employing Cup and Wells method. The study revealed that seeds extracts of Cassia tora in alcohol had good inhibition effect against all the tested organism whereas the herb extracts of Alternanthera Sessilis in petroleum ether and benzene inhibited the growth of all bacteria.